2015
DOI: 10.1007/s00360-015-0927-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body temperature, heart rate, breathing rate, and rate of oxygen consumption, in the tegu lizard (Tupinambis merianae) at various levels of activity

Abstract: The present study determined whether EEG and/or EMG recordings could be used to reliably define activity states in the Brazilian black and white tegu lizard (Tupinambis merianae) and then examined the interactive effects of temperature and activity states on strategies for matching O2 supply and demand. In a first series of experiments, the rate of oxygen consumption (VO2), breathing frequency (fR), heart rate (fH), and EEG and EMG (neck muscle) activity were measured in different sleep/wake states (sleeping, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 56 publications
(68 reference statements)
4
22
0
1
Order By: Relevance
“…Collectively, these results indicate a certain degree of metabolic depression, which is supported by observations in reptiles, including tegu lizards, of a linear correlation between f H and metabolic rate under steady-state conditions (Butler et al, 2002;Piercy et al, 2015). Therefore, gas exchange and f H are seasonally adjusted to match the differing steady-state metabolic demands (Andrade et al, 2004;Clark et al, 2005;Piercy et al, 2015). In fact, hibernation in S. merianae is characterized by an active metabolic reduction during the winter season (Abe, 1983(Abe, , 1995Andrade and Abe, 1999;Lopes and Abe, 1999;de Souza et al, 2004;Sanders et al, 2015), which, in southeastern Brazil, is synchronized with the driest phase of the year.…”
Section: Resting Cardiovascular Variables and Seasonal Variationsupporting
confidence: 78%
See 2 more Smart Citations
“…Collectively, these results indicate a certain degree of metabolic depression, which is supported by observations in reptiles, including tegu lizards, of a linear correlation between f H and metabolic rate under steady-state conditions (Butler et al, 2002;Piercy et al, 2015). Therefore, gas exchange and f H are seasonally adjusted to match the differing steady-state metabolic demands (Andrade et al, 2004;Clark et al, 2005;Piercy et al, 2015). In fact, hibernation in S. merianae is characterized by an active metabolic reduction during the winter season (Abe, 1983(Abe, , 1995Andrade and Abe, 1999;Lopes and Abe, 1999;de Souza et al, 2004;Sanders et al, 2015), which, in southeastern Brazil, is synchronized with the driest phase of the year.…”
Section: Resting Cardiovascular Variables and Seasonal Variationsupporting
confidence: 78%
“…Interestingly, it was recently reported that tegus implanted with a telemetry ECG device and kept under semi-natural conditions anticipate the winter season through a gradual monthly decrease in f H at constant body temperatures (Sanders et al, 2015). Collectively, these results indicate a certain degree of metabolic depression, which is supported by observations in reptiles, including tegu lizards, of a linear correlation between f H and metabolic rate under steady-state conditions (Butler et al, 2002;Piercy et al, 2015). Therefore, gas exchange and f H are seasonally adjusted to match the differing steady-state metabolic demands (Andrade et al, 2004;Clark et al, 2005;Piercy et al, 2015).…”
Section: Resting Cardiovascular Variables and Seasonal Variationmentioning
confidence: 66%
See 1 more Smart Citation
“…Monthly nighttime minimum levels of oxygen consumption were calculated from the formula derived by Piercy et al (2015) from the relationship between heart rate and metabolic rate for this species of tegu lizard under quiescent conditions. The equation used was: log 10 (O 2 consumption) = −1.47 + 0.67 (log 10 (heart rate)).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we record continuously behaviour and T b along with heart and breathing rates as physiological surrogates for metabolism (Zaar et al 2004;Butler et al 2000Butler et al , 2002Clark et al 2004Clark et al , 2006Green et al 2008;Piercy et al 2015), in a group of black and white tegus, T. merianae, housed outdoors under semi-natural conditions. We hypothesized that metabolic suppression (as indicated by changes in heart rate and breathing frequency) would not be evident until the tegus remained in the burrows for extended periods but that metabolism would then progressively fall and be sustained throughout the dormant period.…”
Section: Introductionmentioning
confidence: 99%